ANALISIS USAHA TANI LADA DAN ARAHAN PENGEMBANGANNYA DI KABUPATEN BANGKA TENGAH - Maryadi Maryadi; Atang Sutandi; Ivanocih Agusta (University of Jember, 2016)
Indonesia is the producer of pepper number two in the world after Vietnam. Pepper is one of the leading commodity that has a major role as source of foreign exchange, the source of farmer’s income, and job creation. The high demand on the international market is an opportunity for the development of pepper pepper. In Indonesia, Bangka Belitung Province is a major producer of white pepper which one is the producing regions of District of Bangka Tengah. The development effort pepper plants must be based on land suitability evaluation for optimal production. Moreover, analyzing the feasibility of farming of pepper, analyze marketing margins in the marketing system of white pepper, and arrange referrals pepper plantation development is needed to guide policy makers in Central Bangka Regency. Pepper development requires commitment and effort which is based on plantation development policies implemented proportionately and professionally.